Claudia Poll's Full Stroke at 75 m of Her 200 m Gold Medal Race at the 1998 Perth World Championships - Rushall, B. S.
Video pictures (12 frames) and the appropriate technical/ biomechanical explanations for Claudia Poll's full stroke at 75 m of her 200 m gold medal race at the 1998 Perth World Championships. Good streamlining and continuous force application are obvious strengths in Claudia Poll's two-beat kick stroke. If she tried to fit in a four-beat kick it would alter her arm-stroking pattern markedly, almost asuredly to her detriment. This is a good stroke to emulate particularly in girls/women who like to rate high.